Functional Imaging Reveals Movement Preparatory Activity in the Vegetative State - Bekinschtein, Tristan A.; Manes, Facundo F.; Villarreal, Mirta; Owen, Adrian M.; Della Maggiore, Valeria (Frontiers in Human Neuroscience, 2011)
The Vegetative State (VS) is characterized by the absence of awareness of self or the environment and preserved autonomic functions. The diagnosis relies critically on the lack of consistent signs of purposeful behavior in response to external stimulation. Yet, given that patients with disorders of consciousness often exhibit fragmented movement patterns, voluntary actions may go unnoticed. Here we designed a simple motor paradigm that could potentially detect residual conscious awareness in VS patients with mild to severe brain damage by examining the neural correlates of motor preparation in response to verbal commands. Twenty-four patients who met the diagnostic criteria for VS were recruited for this study. Eleven of these patients showing preserved auditory evoked potentials underwent functional magnetic resonance imaging (fMRI) to test for basic speech processing. Five of these patients, who showed word related activity, were included in a second fMRI study aimed at detecting functional changes in premotor cortex elicited by specific verbal instructions to move either their left or their right hand. Despite the lack of overt muscle activity, two patients out of five activated the dorsal premotor cortex contralateral to the instructed hand, consistent with movement preparation. Given that movement preparation in response to a motor command is a sign of purposeful behavior, our results are consistent with residual conscious awareness in these patients. We believe that the identification of positive results with fMRI using this simple task, may complement the clinical assessment by helping attain a more precise diagnosis in patients with disorders of consciousness.